Future of Carbon Storage in the Yangtze River Basin, China under Alternative Climate and Land-Use Pathways - Qi Zhang; Guanshi Zhang; Xiu Zhang; Dongsheng Liu; Ruying Fang; Na Dong; Hongjuan Wu; Sen Li (Ecosystem Health and Sustainability, 2023)
While the Chinese government has put a strong emphasis on combating climate change and pledged to strive for “carbon neutrality” in the 2060s, it is fundamental to assess the likely evolution of carbon storage in China’s terrestrial ecosystems. Here, we conducted a simulation study grounded by recent empirical evidence and advances in modeling techniques to project the spatiotemporal dynamics of carbon storage of the Yangtze River Basin (YRB)’s ecosystem from 2015 to 2050. Two sets of scenarios were developed to analyze the plausible effects of land-use change, climatic change, and carbon policy on carbon dynamics. The results show that the estimated total carbon storage of the YRB’s ecosystem was 21.75 Pg C in 2015, accounting for about a quarter of the total in China. Model simulations projected an overall increase in carbon storage of the YRB’s ecosystem. Under the combined scenarios, land-use change and climate change contributed to total carbon sequestration by 1.45 to 2.02 PgC and 1.64 to 2.00 PgC, respectively. Under the carbon tax scenario, due to an increase in the extent of forest driven by different carbon regimes, the YRB was projected to absorb 1.26 to 2.32 PgC by 2050. Several regions had been projected under threats of severe carbon losses, including a few places with high present-day carbon density in the middle reaches of the YRB. Our results could provide a more complete picture of carbon sequestration potential of the YRB’s ecosystems, which could benefit the formulation of nature-based solutions.